5. CHARACTERISTICS OF CHILDREN WITH CYANOTIC CONGENITAL HEART DISEASE AT CHILDREN'S HOSPITAL 2 FROM JANUARY 1, 2024 TO DECEMBER 31, 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the epidemiological, clinical, paraclinical, and treatment characteristics of children with cyanotic congenital heart disease (CCHD) at Children’s Hospital 2 during 2024.Method: Descriptive case series.Results: A total of 192 children with CCHD were included. Male patients accounted for 54.2%. The mean age was 28.4 ± 37.4 months; the
Keywords: Congenital heart disease, Children’s Hospital 2.